Practices of Deduction and Induction in the ELT Classroom: A Case Study - Poudel, Kamal Kumar (Kanakai Journal, 2022)
Deductive and inductive approaches are very well-articulated notions in the literature of teaching and learning grammar. This article first conceptualizes deduction and induction from a broader perspective, thereby connecting them to inductive and deductive approaches to teaching grammar. The case study this article draws from was based on the observation of two contextually similar classroom presentations– the first deductive and the next inductive– of an 'outstanding' student teacher as a separate model of each, aiming basically at sketching a comprehensive picture illustrating the classroom actualization of each of these approaches. Comparing the two models, it can be concluded that, regarding teaching and learning grammar, induction aligns more closely to the overall pedagogic essence than deduction does. As a future direction, the study can/should be extended to broader contexts in terms of participants and cases so as to obtain more comprehensive data, hence more reliable results.